Gatifloxacin Induces S and G2-Phase Cell Cycle Arrest in Pancreatic Cancer Cells via p21/p27/p53 - Yadav, Vikas; Sultana, Sarwat; Yadav, Jyoti; Saini, Neeru (PLOS ONE, 2012)
Pancreatic cancer, despite being the most dreadful among gastrointestinal cancers, is poorly diagnosed, and further, the situation has been aggravated owing to acquired drug resistance against the single known drug therapy. While previous studies have highlighted the growth inhibitory effects of older generation fluoroquinolones, the current study aims to evaluate the growth inhibitory effects of newer generation fluoroquinolone, Gatifloxacin, on pancreatic cancer cell lines MIA PaCa-2 and Panc-1 as well as to elucidate the underlying molecular mechanisms. Herein, we report that Gatifloxacin suppresses the proliferation of MIA PaCa-2 and Panc-1 cells by causing S and G2-phase cell cycle arrest without induction of apoptosis. Blockade in S-phase of the cell cycle was associated with increased TGF-β1 expression and translocation of Smad3-4 complex to the nucleus with subsequent activation of p21 in MIA PaCa-2 cells, whereas TGF-β signalling attenuated Panc-1 cells showed S-phase arrest by direct activation of p27. However, Gatifloxacin mediated G2–phase cell cycle arrest was found to be p53 dependent in both the cell lines. Our study is of interest because fluoroquinolones have the ability to penetrate pancreatic tissue which can be very effective in combating pancreatic cancers that are usually associated with loss or downregulation of CDK inhibitors p21/p27 as well as mutational inactivation of p53. Additionally, Gatifloxacin was also found to synergize the effect of Gemcitabine, the only known drug against pancreatic cancer, as well as the broad spectrum anticancer drug cisplatin. Taken together our results suggest that Gatifloxacin possesses anticancer activities against pancreatic cancer and is a promising candidate to be repositioned from broad spectrum antibiotics to anticancer agent.